Investigating the Impact of Spirituality, Support for Innovation, Self-Efficacy and Job Satisfaction on Employee’s Ethical Behaviour - Chauhan, Hemant; Jaglan, Vivek (International Journal of Psychosocial Rehabilitation, 2020)
This study examined the impact of spirituality, job satisfaction, self-efficacy, and support for innovation on employees’ ethical behavior. The sample was collected from employees working in various hospitals in the Maharashtra region. Using structural equation modeling, the results suggest that spirituality, job satisfaction, self-efficacy, and support for innovation impact consumer ethical behavior. Accordingly, this investigation underpins the possibility that considered variables relate to employees desire to display ethical behavior. The finding may help companies in nurturing ethical behavior among employees.